26=3w-10

Simple and best practice solution for 26=3w-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26=3w-10 equation:


Simplifying
26 = 3w + -10

Reorder the terms:
26 = -10 + 3w

Solving
26 = -10 + 3w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-3w' to each side of the equation.
26 + -3w = -10 + 3w + -3w

Combine like terms: 3w + -3w = 0
26 + -3w = -10 + 0
26 + -3w = -10

Add '-26' to each side of the equation.
26 + -26 + -3w = -10 + -26

Combine like terms: 26 + -26 = 0
0 + -3w = -10 + -26
-3w = -10 + -26

Combine like terms: -10 + -26 = -36
-3w = -36

Divide each side by '-3'.
w = 12

Simplifying
w = 12

See similar equations:

| 2s-6=4 | | 9w/3 | | 2w+13=29 | | X^2+2x+y^2-10=0 | | 49=4v+9 | | -1=x/15 | | 3u-8=40 | | 5d+3=18 | | 5x+3=-x-21 | | 5n-1+5n-3=26 | | h=372/(3x*x) | | 2x+5+c=0 | | x-x^2-2x=0 | | 14x-5+5-12x= | | 100x+500y=400 | | b(b+2)=4 | | 2-3=10 | | (m*(m-1))/2 | | 4m^2+30m+16=0 | | -7x-2=-6x+3 | | m*(m-1)*(m-2)/6 | | 7x-56=-6x+21 | | 8x^2+6x+1+0=0 | | t/7=6/42 | | 8-2x+3=2x+5 | | 5/h=15/12 | | -3x+3=7x-4 | | -(5x-3x)+x=21 | | 2tan-3=-5 | | 1+0.5x=x^2-6x+9 | | 7x+21=4x-5 | | 4cos+1=2cos |

Equations solver categories